Consumers’ attitudes towards modern solutions in the retail trade - Maciejewski, Grzegorz (Economics and Business Review, 2018)
The aim of the article is to present consumer attitudes in Poland in respect of modern solutions in the retail trade and the influence which these attitudes have on their behaviour in the market. The considerations were conducted using methods of logical inference, based on a critical analysis of available derivative sources and conclusions from quantitative research conducted on a sample of 1.075 consumers. In order to analyse more deeply the research results a cluster analysis was conducted using one of the hierarchical methods – the Ward’s method. Respondents’ attitudes towards modern solutions in the retail trade are generally positive. However they are not always recognized by them. A large percentage of respondents declared that they are not acquainted with particular forms of modern retail trade (mostly Beacon, PSS or RIFID systems). They were mostly consumers from the ‘retreated skeptics’ group, in other words the elderly with basic or vocational education from small towns and villages. The research findings presented may be used by trade enterprises in order to answer to the identified need of consumers from generation Z and to set out the direction of the technological education of consumers and increase the availability of particularised solutions.